A QUALITATIVE STUDY DISCOVERING THE COMMON MEDICATION-THERAPY PROBLEMS IN PATIENTS WITH TYPE 2 DIABETES MELLITUS (T2DM) IN INDONESIA - Wahyuningrum, Retno; Wahyono, Djoko; Mustofa, Mustofa; Prabandari, Yayi Suryo (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Type 2 diabetes mellitus (T2DM) is a chronic and non-communicable diseases caused by insulin resistance. The management of the disease is not only carried out by administering pharmacological therapies, but also non-pharmacological. The aim of the overall study was to develop a model to improve the quality of counseling practice in pharmacies. The research question addressed in this substudy was to identify the medication therapy problems (MTPs) of T2DM. Methods: A total of 42 participants were interviewed between November 2015 and May 2016 through semi-structured surveys. Face-to-face interviews were conducted with patients who visited the internal clinic in the three general hospitals at Yogyakarta. It emphasized on the patient's drug-related experiences, knowledge, perceptions, problems, and actions. The analysis was done thematically using the interpretative phenomenological analysis technique. Results: The average age of participants was 57.7 years, and more than half were women (55.5%). The most common therapy-related problems are related to individual factors, in term of inappropriate lifestyle choices, which include smoking, having a body mass index value over 25, lack of exercise, lack of knowledge about the nature of their disease, some did not know about the influence of foods on blood glucose level, the effect of the medicines on the disease and/or complications. The interviewees had realized that psychological stress enhanced their blood glucose. Conclusion: Pharmacists need to pay attention to the management of non-pharmacological when giving advice to patients with T2DM. Â